2015
DOI: 10.1177/1533317515576387
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between 11C-PIB-PET and Clinical Diagnosis in a Memory Clinic

Abstract: This study demonstrates that detecting in vivo amyloid plaques by molecular imaging is considerably frequent in most of the dementia syndromes and shows that there are frequent discordance between molecular diagnosis and clinical assumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The Aβ positivity rate for aMCI (64.7%) observed in this study was very similar to the rates reported in previous studies, which ranged from 57.9% to 67.9%. [9][10][11][12] In regard of the Aβ As various factors including demographic variables, study settings, PET ligands used to measure cerebral Aβ, and the definition or threshold for Aβ positivity may influence on the rate, so it is not easy to directly compare it between the studies. Nevertheless, as shown in our study, the Aβ positivity rate of aMCI was higher than that of naMCI across all the studies, consistent with clinical observation that higher proportion of individuals progressed to AD dementia in aMCI than in naMCI.…”
Section: Discussionmentioning
confidence: 99%
“…The Aβ positivity rate for aMCI (64.7%) observed in this study was very similar to the rates reported in previous studies, which ranged from 57.9% to 67.9%. [9][10][11][12] In regard of the Aβ As various factors including demographic variables, study settings, PET ligands used to measure cerebral Aβ, and the definition or threshold for Aβ positivity may influence on the rate, so it is not easy to directly compare it between the studies. Nevertheless, as shown in our study, the Aβ positivity rate of aMCI was higher than that of naMCI across all the studies, consistent with clinical observation that higher proportion of individuals progressed to AD dementia in aMCI than in naMCI.…”
Section: Discussionmentioning
confidence: 99%
“…Even though only nine countries in the LAC region have cyclotrons for the production of radiotracers, the access to PET in the region has improved in the last few years, with an annual growth of ∼21% (7,8). Access to amyloid tracers has also improved and the proposed A-T-N criteria are increasingly being applied to classify the patients in research studies (19,20,(39)(40)(41)(42)(43)(44). Regarding the clinical utility of amyloid PET, Chrem Mendez et al described 76.2% concordance of 11 C-PIB PET with baseline diagnosis in patients with AD, and a range of concordance of 54.5-100% in other forms of cognitive impairment (19).…”
Section: Discussionmentioning
confidence: 99%
“…Access to amyloid tracers has also improved and the proposed A-T-N criteria are increasingly being applied to classify the patients in research studies (19,20,(39)(40)(41)(42)(43)(44). Regarding the clinical utility of amyloid PET, Chrem Mendez et al described 76.2% concordance of 11 C-PIB PET with baseline diagnosis in patients with AD, and a range of concordance of 54.5-100% in other forms of cognitive impairment (19). It is important to emphasize on the complementary role of 18 F-FDG and 11 C-PIB in the diagnosis of patients with dementia, since the patterns of hypometabolism on the 18 F-FDG scan can help to distinguish between different clinical entities in amyloid negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…18 In 2015, amyloid PET scan utility was studied in the clinical setting, showing agreement between 11C-PIB-PET findings and clinical diagnosis. 19 A retrospective study including 144 patients (40 from the Argentine ADNI), divided patients into clinical categories of high or low probability of AD pathology. The former included: amnestic MCI; amnestic multi-domain MCI; dementia of Alzheimer's Type (DAT); posterior cortical atrophy (PCA); logopenic PPA; cerebral amyloid angiopathy; as well as mixed dementia.…”
Section: Fleni Experience: Multimodal Approach and International Networkmentioning
confidence: 99%
“…The study demonstrated the importance of detecting in vivo amyloid plaque deposition using molecular imaging in atypical patients, such as in cases of early-onset dementia, PCA, PPA, and non-amnesic MCI. 19 A cross-sectional analysis of baseline data revealed links between episodic memory performance, hippocampal volume, and other biomarkers. 20 Furthermore, the combination of recognition discrimination index and Delayed Recall test results proved useful to predict conversion from MCI to dementia.…”
Section: Fleni Experience: Multimodal Approach and International Networkmentioning
confidence: 99%